Polarized Ultrathin BN Induced Dynamic Electron Interactions for Enhancing Acidic Oxygen Evolution - Hao, Yixin; Hung, Sung‐Fu; Tian, Cheng; Wang, Luqi; Chen, Yi‐Yu; Zhao, Sheng; Peng, Kang‐Shun; Zhang, Chenchen; Zhang, Ying; Kuo, Chun‐Han; Chen, Han‐Yi; Peng, Shengjie (Angewandte Chemie, 2024)
Developing ruthenium‐based heterogeneous catalysts with an efficient and stable interface is essential for enhanced acidic oxygen evolution reaction (OER). Herein, we report a defect‐rich ultrathin boron nitride nanosheet support with relatively independent electron donor and acceptor sites, which serves as an electron reservoir and receiving station for RuO2, realizing the rapid supply and reception of electrons. Through precisely controlling the reaction interface, a low OER overpotential of only 180 mV (at 10 mA cm−2) and long‐term operational stability (350 h) are achieved, suggesting potential practical applications. In situ characterization and theoretical calculations have validated the existence of a localized electronic recycling between RuO2 and ultrathin BN nanosheets (BNNS). The electron‐rich Ru sites accelerate the adsorption of water molecules and the dissociation of intermediates, while the interconnection between the O‐terminal and B‐terminal edge establishes electronic back‐donation, effectively suppressing the over‐oxidation of lattice oxygen. This study provides a new perspective for constructing a stable and highly active catalytic interface. The lattice‐matched interface between defect‐rich ultrathin boron nitride nanosheets (BNNS) and RuO2 is ingeniously constructed to achieve robust acidic oxygen evolution reaction (OER) activity and stability, due to the directional electron transfer of interface from B and N vacancies to RuO2.